2000
DOI: 10.1038/sj.ejcn.1601074
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, dietary calcium and vitamin D deficiency in women: a population-based study

Abstract: Objective: To determine differences in dietary calcium and vitamin D intakes between female never, former and current smokers. Design: Population-based survey using a validated food frequency questionnaire. Setting: The Bus Sante  2000, epidemiologic observatory of Geneva, Switzerland. Subjects: 2319 women resident in Geneva, Switzerland between 1993 and 1997. Results: Daily calcium intake was 798 mg among current heavy smokers ( 20 cigarettesaday), 882 mg among current moderate smokers (1 ± 19 cigarettesaday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 52 publications
3
27
1
Order By: Relevance
“…Niacin intake was significantly lower in smokers only for US men. Other studies have reported both higher 1,2,11 and lower 1,2,13,17,35 intakes of vitamin D in smokers compared to nonsmokers. Vitamin B 12 intake has generally not varied by smoking status.…”
Section: Discussionmentioning
confidence: 89%
“…Niacin intake was significantly lower in smokers only for US men. Other studies have reported both higher 1,2,11 and lower 1,2,13,17,35 intakes of vitamin D in smokers compared to nonsmokers. Vitamin B 12 intake has generally not varied by smoking status.…”
Section: Discussionmentioning
confidence: 89%
“…The recent dietary survey of Morabia et al (2000) failed to specify an intake that they would have considered adequate. Morabia et al simply concluded that heavy smokers were more prone to vitamin D de®ciency because their mean vitamin D intake of 1.92 mgaday was statistically less than the mean intake of 2.39 mgaday for non-smokers.…”
Section: Specify a Suitable Target For Vitamin D Nutritional Adequacymentioning
confidence: 99%
“…Recent issues of this journal have seen two articles highlighting the nutritional need for vitamin D in adults (Schaafsma et al, 2000;Morabia et al, 2000). This editorial is a critical commentary with suggested strategies to make publications relating to vitamin D requirements of practical bene®t to others.…”
Section: Introductionmentioning
confidence: 99%
“…This is precisely why we focused on differential intakes according to smoking status. The goal of our study (Morabia et al, 2000) has been inaccurately summarized by Vieth and Carter (Vieth & Carter, 2001). We have reported that salmon, 45% fat cheese, margarine and eggs are the most important sources of vitamin D in the Geneva population.…”
mentioning
confidence: 99%
“…The comments on our paper (Morabia et al, 2000) in the editorial by Vieth and Carter (Vieth & Carter, 2001) re¯ect an unfortunately common misinterpretation of epidemiologic data.…”
mentioning
confidence: 99%